Francophonie et identités culturelles - Albert, Christiane (Karthala, 1999)
L'expression littéraire est un acte puissant par lequel un être construit son identité à la fois individuellement et collectivement. Dans le contexte de la francophonie, cet acte identitaire est d'autant plus paradoxal que la langue utilisée est le français et que la littérature francophone émerge, lors de la colonisation, dans un environnement multiculturel, à partir de la déconstruction d'une littérature dominante. Afin d'interroger les multiples processus intervenant dans la constitution de l'identité francophone, un colloque a eu lieu à l'université de Pau en 1998. Il s'est achevé par une table ronde qui a réuni trois écrivains francophones : Rachid Boudjedra, Pius Ngandu Nkaashama et Tierno Monénembo qui ont évoqué la relation qu'ils entretiennent avec la langue et l'écriture. Cet ouvrage rassemble les interventions des participants à ce colloque. Tout au long de ces journées, l'identité francophone est apparue comme une configuration d'éléments multiples où la langue remplit une fonction importante. Elle ne suffit cependant pas à fonder le discours identitaire dans la mesure où elle n'est qu'un isntrument au service des écrivains. D'autres éléments apparaissent, en effet, déterminants dans l'élaboration de cette identité, éléments indissociables de l'Histoire et des développements propres à chaque société. De ce fait, l'espace littéraire francophone apparaît décentré par rapport à la langue française car il fait entendre de nouvelles voix à la périphérie de l'aire linguistique du français. Ce qui démontre, si cela était nécessaire, la richesse et la complexité de la littérature francophone, qui constitue d'une certaine façon, le laboratoire de la culture post-moderne du vingt-et-unième siècle.
Keywords: 1800-1899; 1900-1999; afrique; approches et analyses; colonialisme; cours; discipline; fem1000; francophonie; haïti; identités culturelles; langage; postcolonialisme; postmodernisme; premier cycle; périodes historiques; ressource en ligne; régions géographiques; thématiques; violences; études littéraires

L'histoire de Bone - Allison, Dorothy (Collection 10/18, 1999)
En Caroline du Sud, les étés sont étouffants. Les soirées se passent sur la véranda, à boire du thé glacé et à raconter des histoires. Ruth Anne Boatwright, surnommée Bone par sa famille et estampillée " bâtarde " par le comté de Greenville, se souvient. Elle revoit sa grand-mère édentée, impertinente, ses tantes farouches, usées par leurs grossesses, ses oncles violents, ivrognes pris au piège de leur misère. Elle se souvient de l'amour qu'elle portait à sa mère et de la haine grandissante qu'elle éprouvait pour son beau-père. Elle se souvient et elle raconte, avec une brutale sincérité, les aspirations d'une petite fille, la violence insoutenable, l'amour obstiné. Ce premier roman largement autobiographique, écrit pour exorciser cette enfance brûlée, a été finaliste pour le National Book Award en 1992
Keywords: 1900-1999; 1950-1959; amériques; approches et analyses; inceste; inégalités; périodes historiques; régions géographiques; systèmes d'oppressions; thématiques; violences; états-unis

Pretty in punk: girls' gender resistance in a boys' subculture - Leblanc, Lauraine (Rutgers University Press, 1999)
Pretty in Punk combines autobiography, interviews, and sophisticated analysis to create the first insider's examination of the ways punk girls resist gender roles and create strong identities.Why would an articulate, intelligent, thoughtful young women shave off most of her hair, dye the remainder green, shape it into a mohawk, and glue it onto her head? What attracts girls to male-dominated youth subcultures like the punk movement? What role does the subculture play in their perceptions of themselves, and in their self-esteem? How do girls reconcile a subcultural identity that is deliberately coded “masculine” with the demands of femininity?Research has focused on the ways media and cultural messages victimize young women, but little attention has been paid to the ways they resist these messages. In Pretty in Punk, Lauraine Leblanc examines what happens when girls ignore these cultural messages, parody ideas of beauty, and refuse to play the games of teenage femininity. She explores the origins and development of the punk subculture, the processes by which girls decide to “go punk,” patterns of resistance to gender norms, and tactics girls use to deal with violence and harassment.Pretty in Punk takes readers into the lives of girls living on the margins of contemporary culture. Drawing on interviews with 40 girls and women between the ages of 14-37, Leblanc examines the lives of her subjects, illuminating their forms of rebellion and survival. Pretty in Punk lets readers hear the voices of these women as they describe the ways their constructions of femininity—from black lipstick to slamdancing—allow them to reject damaging cultural messages and build strong identities. The price they pay for resisting femininity can be steep—girls tell of parental rejection, school expulsion, institutionalization, and harassment. Leblanc illuminates punk girls' resistance to adversity, their triumphs over tough challenges, and their work to create individual identities in a masculine world.
Keywords: 1900-1999; 1990-1999; amériques; approches et analyses; atlanta; culture populaire; entretien; ethnographie; genre; harcèlement sexuel; montréal; nouvelle-orléans; patriarcat; périodes historiques; régions géographiques; résistance; san francisco; stéréotypes de genre; systèmes d'oppressions; thématiques; violences

Des droits à reconnaître: les lesbiennes face à la discrimination - Bonneau, Micheline; Demczuk, Irène (Collection Les Entêtées, 1998)
Regroupant recherches et analyses, témoignages et récits personnels, ce livre rend compte de la discrimination vécue par les lesbiennes. Malgré que le Québec ait adopté une Charte des droits de la personne qui interdit toute discrimination basée sur l'orientation sexuelle, il faut reconnaître que l'adoption de ce principe d'équité n'a pas fait disparaître toute trace d'hétérosexisme dans la société. Les lesbiennes ne bénéficient pas encore d'une égalité juridique formelle, encore moins réelle.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; cours; discipline; discours dominant; droits des femmes*; hétéronormativité; hétérosexisme; identités LGBTQIA2+; inégalités; lesbianisme; lesbophobie; premier cycle; périodes historiques; queer; québec; régions géographiques; sciences humaines; sexualité; shm4000; soc2014; sociologie; systèmes d'oppressions; thématiques; violences

La conquête d'un espace public : les bars fréquentés par les lesbiennes - Chamberland, Line (Sortir de l'ombre : histoires des communautés lesbienne et gaie de Montréal, 1998)
Histoire bien documentée et inédite des communautés homosexuelles de Montréal. Longtemps victimes de brimades et de préjugés, les gais et lesbiennes sont finalement "sorti.e.s de l'ombre" et ont gagné de belles victoires durant les dernières décennies.
Keywords: LGBTQIA2+; amériques; approches et analyses; cours; his4860; histoire et politique; hétérosexisme; identités LGBTQIA2+; lesbianisme; lesbiennes; montréal; premier cycle; québec; rapports sociaux de sexe; régions géographiques; sexualité; systèmes d'oppressions; thématiques; violences

Sortir de l'ombre : histoires des communautés lesbienne et gaie de Montréal - Demczuk, Irène; Remiggi, Frank William (Des hommes et des femmes en changement, 1998)
Histoire bien documentée et inédite des communautés homosexuelles de Montréal. Longtemps victimes de brimades et de préjugés, les gais et lesbiennes sont finalement "sorti.e.s de l'ombre" et ont gagné de belles victoires durant les dernières décennies.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; cours; discipline; discours dominant; his4860; histoire et politique; hétéronormativité; hétérosexisme; identités LGBTQIA2+; lesbianisme; montréal; premier cycle; périodes historiques; queer; québec; régions géographiques; sexualité; shm4000; soc2014; systèmes d'oppressions; thématiques; violences

Feminist visions of development: Gender analysis and policy - Jackson, Cecile; Pearson, Ruth (Routledge, 1998)
Dans le sillage de la 4e Conférence mondiale sur les femmes, cet ouvrage réunit des spécialistes de premier plan du genre et du développement qui interrogent les vingt dernières années de travaux dans ce domaine. Visions féministes du développement jette un nouvel éclairage sur des questions clés telles que : * le genre et l'environnement * l'éducation * la population * les droits reproductifs * l'industrialisation * la politique macroéconomique * la pauvreté. Inspiré par les travaux théoriques féministes récents, il réexamine les analyses structurelles antérieures et ouvre la voie à de nouvelles recherches dans ce domaine.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; droits des femmes*; projet charge mentale; périodes historiques; santé; thématiques; travail; violences

Lessons from the intersexed - Kessler, Suzanne J. (Rutgers University Press, 1998)
From the moment intersexuality-the condition of having physical gender markers (genitals, gonads, or chromosomes) that are neither clearly female nor male-is suspected and diagnosed, social institutions are mobilized in order to maintain the two seemingly objective sexual categories. Infants' bodies are altered, and what was "ambiguous" is made "normal." Kessler's interviews with pediatric surgeons and endocrinologists reveal how the intersex condition is normalized for parents and she argues that the way in which intersexuality is managed by the medical and psychological professions displays our culture's beliefs about gender and genitals. Parents of intersexed children are rarely heard from, but in this book they provide another perspective on reasons for genital surgeries and the quality of medical and psychological management. Although physicians educate parents about how to think about their children's condition, Kessler learned from parents of intersexed children that some parents are able to accept atypical genitals. Based on analysis of the medical literature and interview with adults who had received treatment as interesexed children, Kessler proposes new approaches for physicians to use in talking with parents and children. She also evaluates the appearance of a politicized vanguard, many of who are promoting an intersexual identity, who seek to alter the way physicians respond to intersexuality. Kessler explores the possibilities and implications of suspending a commitment to two "natural" genders and addresses gender destabilization issues arising from intersexuality. She thus compels readers to re-think the meaning of gender, genitals, and sexuality.
Keywords: LGBTQIA2+; approches et analyses; capacitisme; care; corps; cours; discipline; ethnographie; intersexuation; premier cycle; psychologie; santé; sciences humaines; soc2014; système de genre; systèmes d'oppressions; thématiques; violences; violences médicales

Quand la violence parle du sexe : analyse du discours thérapeutique pour hommes violents - Letarte, Lise (Université du Québec à Montréal, 1998)
Keywords: IREF; amériques; discipline; hommes* violents; mémoires/thèses; québec; régions géographiques; sciences humaines; sexologie; thématiques; violences; violences contre les femmes*

Inside the academy and out: lesbian/gay/queer studies and social action - Ristock, Janice L.; Taylor, Catherine G. (University of Toronto Press, 1998)
Inside the Academy and Out demonstrates that the pedagogical and theoretical insights offered by lesbian/gay/queer studies can have relevance to a broader social sphere. The essayists represented here come from a wide range of disciplines, including English, education, philosophy, sociology, and women's studies. Their essays are divided into two broad areas: 'Pedagogy and Research' and 'Spheres of Action.' Taken together, they explore teaching and research theory, examining their implications in areas such as AIDS education, social services, law reform, and popular culture.
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; approches et analyses; cours; discipline; droit; ethnographie; intersectionnalité; justice sociale; militance; premier cycle; pédagogie; périodes historiques; queer; santé; science politique et droit; sciences de l'éducation; sciences humaines; sexologie; soc2014; thématiques; violences

The flowers in your dustbin: Girls in the North American punk subcultures of the 1990s - Leblanc, Lauraine (Université Emory, 1997)
Girls in male-dominated youth subcultures confront ideologies of gender which remain largely invisible and often tacitly accepted in many women's everyday lives. Punk girls choose to construct their femininity within a highly male-dominated, "masculinist," context; girls are present in such youth subcultures, but the masculine definition of their norms problematizes their participation. Thus, punk girls struggle to accommodate female gender norms within subcultural identities which are deliberately coded as "masculine." Although young women in America encounter the norms of the female gender role on a daily basis, punk girls' negotiations between the norms of femininity and those of punk open these prescriptions to critical examination which they might not otherwise be accorded. In this dissertation, I explore accounts of punk girls' engagements with both mainstream and subcultural gender norms. In constructing this account of girls' lived experiences in the punk subculture, I rely primarily upon the phenomenology, or experiential narrative, of punk girls' everyday lives. I elicited these accounts within the context of conducting participant observation in the punk scenes of four North American cities (Atlanta, Montreal, New Orleans, and San Francisco) from 1993 to 1995, conducting ethnographic interviews with forty punk girls. In the following, I explore various facets of punk girls' engagements with gender norms, including punk girls' narratives of engagement with the subculture; the construction of punk as a discourse of masculinity; punk girls' stylistic, behavioral, and discursive reconstructions of femininity; punk girls' experiences of public harassment and sexual harassment, and their strategic responses to these. I argue that these girls use the punk subculture in order to carry out resistances to varied forms of gender oppression, thereby developing stronger self-concepts in the face of adversity.
Keywords: 1900-1999; 1990-1999; amériques; approches et analyses; atlanta; discipline; ethnographie; genre; harcèlement sexuel; masculinisme; montréal; mémoires/thèses; nouvelle-orléans; patriarcat; philosophie; périodes historiques; régions géographiques; résistance; san francisco; sciences humaines; systèmes d'oppressions; thématiques; violences

Mémoires lesbiennes : le lesbianisme à Montréal entre 1950 et 1972 - Chamberland, Line (De mémoire de femmes, 1996)
Line Chamberland retrace la vie de femmes qui ont eu le courage de leurs amours à une époque où la condamnation sociale du lesbianisme était unanime. À partir de nombreux témoignages, l’auteure démontre de quelle façon s’exerçait le contrôle social du lesbianisme, quel rôle jouait la famille et comment diverses instances comme les institutions religieuses, l’appareil judiciaire et les autorités psychomédicales veillaient à ce que ces femmes se conforment aux diktats, les poussant parfois à la marginalité ou les obligeant à adopter diverses stratégies de dissimulation.
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; cours; discipline; droits des femmes*; histoire et politique; hétéronormativité; hétérosexisme; identités LGBTQIA2+; lesbianisme; montréal; pol4212; premier cycle; périodes historiques; queer; québec; régions géographiques; sexualité; shm4000; systèmes d'oppressions; thématiques; violences

Science, conscience et action : vingt-cinq ans de recherche féministe au Québec - Dagenais, Huguette (Les éditions du remue-ménage, 1996)
Après un quart de siècle de néoféminisme, on connaît encore mal la recherche féministe et l’ampleur du travail accompli par ces chercheuses. Les auteures examinent ici les travaux qui ont porté sur la famille, la conciliation travail-famille et sur l’emploi, ceux qui ont documenté des aspects particuliers de la santé des femmes et de la violence conjugale ainsi que les nombreuses études produites dans le domaine de l’éducation. Elles mettent également en lumière les changements et les résistances révélés par les recherches dans le champ religieux, le champ politique, celui du droit de même que dans le domaine des communications. Ce faisant, elles rendent manifestes les caractéristiques de la recherche féministe québécoise, notamment les liens établis par les chercheuses entre théorie et pratique, recherche et action. Des textes de Pierrette Bouchard, Anita Caron, Renée Cloutier, Christine Corbeil, Huguette Dagenais, René B.-Dandurand, Francine Descarries, Louise Guyon, Thérèse Hamel, Geneviève Martin, Karen Messing, Josée Néron, Ann Robinson, Armande Saint-Jean, Diane-Gabrielle Tremblay et Manon Tremblay.
Keywords: 1900-1999; amériques; conciliation famille-travail; cours; discipline; droit; famille; fem1000; histoire et politique; premier cycle; périodes historiques; québec; régions géographiques; santé; science des religions; science politique; science politique et droit; sciences humaines; thématiques; théologie; violences; violences contre les femmes*

Taboo: Sex, identity, and erotic subjectivity in anthropological fieldwork - Kulick, Don; Willson, Margaret (Routledge, 1995)
Taboo looks at the ethnographer and sexuality in anthropological fieldwork and considers the many roles that sexuality plays in the anthropological production of knowledge and texts. How does the sexual identity that anthropologists have in their "home" society affect the kind of sexuality they are allowed to express in other cultures? How is the anthropologists' sexuality perceived by the people with whom he or she does research? How common is sexual violence and intimidation in the field and why is its existence virtually unmentioned in anthropology? These are but a few of the questions to be confronted, exploring from differing perspectives the depth of the influence this tabooed topic has on the entire practice and production of anthropology. A long-overdue text for all students and lecturers of anthropology, many post-fieldwork readers will find a resonance of issues they have previously faced (or tried to avoid) and those who are still to undertake fieldwork will find articles that refer to other kinds of personal and professional experience as well as providing invaluable preparations for coping in the field.other kinds of personal and professional experience as well as providing invaluable preparations for coping in the field.other kinds of personal and professional experience as well as providing invaluable preparations for coping in the field.other kinds of personal and professional experience as well as providing invaluable preparations for coping in the field.
Keywords: anthropologie; discipline; identités; ressource en ligne; sciences humaines; sexualité; thématiques; violences; violences sexuelles

Fatal women: Lesbian sexuality and the mark of aggression - Hart, Lynda (Princeton University Press, 1994)
Partant du lien historique entre criminalité et déviance sexuelle, Lynda Hart construit une théorie complexe et originale dans laquelle l'ombre de la lesbienne anime les représentations des femmes violentes dans la littérature, les pièces de théâtre, les films et les performances. Les chapitres détaillent cette théorie dans divers domaines, notamment : * Lulu Plays de Frank Wedekind * Thelma and Louise et Basic Instinct * l'art de la performance de Karen Finley dans le contexte des débats sur la censure * La performance des Split Britches, Lesbians Who Kill Fatal Women, est une contribution majeure à la théorie lesbienne et aux études culturelles. C'est une étude stimulante et enrichissante.
Keywords: arts; discipline; histoire et politique; personnes lesbiennes; ressource en ligne; sexualité; thématiques; violences; études culturelles; études littéraires

The Lesbian and gay studies reader - Abelove, Henry; Barale, Michèle Aina; Halperin, David M. (Routledge, 1993)
Rassemblant quarante-deux essais révolutionnaires, dont beaucoup sont déjà des classiques, The Lesbian and Gay Studies Reader fournit une introduction indispensable à l'état contemporain des études lesbiennes/gay, illustrant largement l'étendue, la portée, la diversité, l'attrait et puissance du travail actuellement réalisé dans le domaine. Présentant des essais d'éminents chercheurs tels que Judith Butler, John D'Emilio, Kobena Mercer, Adrienne Rich, Gayle Rubin et Eve Kosofsky Sedgwick, The Lesbian and Gay Studies Reader explore une multitude d'expériences sexuelles, ethniques, raciales et socio-économiques. . S'étendant sur des disciplines telles que l'histoire, la littérature, la théorie critique, les études culturelles, les études afro-américaines, les études ethniques, la sociologie, l'anthropologie, la psychologie, les classiques et la philosophie, cette anthologie retrace l'inscription des significations sexuelles dans toutes les formes d'expression culturelle. Représentant le meilleur et le plus important travail en langue anglaise dans le domaine, The Lesbian and Gay Studies Reader aborde des sujets tels que les rôles butch-fem, la construction culturelle du genre, le séparatisme lesbien, la théorie féministe, le sida, l'éducation sexuelle sans risque, le colonialisme, le S /M, Oscar Wilde, Gertrude Stein, les livres pour enfants, le nationalisme noir, les films populaires, Susan Sontag, le placard, l'homophobie, Freud, Sappho, les médias, les hijrasde l'Inde, Robert Mapplethorpe, et la politique de représentation. Il contient également un essai bibliographique détaillé qui fournira aux lecteurs un guide inestimable pour des lectures complémentaires. Contributeurs :Henry Abelove, Tomas Almaguer, Ana Maria Alonso, Michele Barale, Judith Butler, Sue-Ellen Case, Danae Clark, Douglas sertissage, Teresa de Lauretis, John D'Emilio, Jonathan Dollimore, Lee Edelman, Marilyn Frye, Charlotte Furth, Marjorie Garber , Stuart Hall, David Halperin, Phillip Brian Harper, Gloria T. Hull, Maria Teresa Koreck, Audre Lorde, Biddy Martin, Deborah E. McDowell, Kobena Mercer, Richard Meyer, DA Miller, Serena Nanda, Esther Newton, Cindy Patton, Adrienne Rich, Gayle Rubin, Joan W. Scott, Daniel L. Selden, Eve Kosofsky Sedgwick, Barbara Smith, Catharine R. Stimpson, Sasha Torres, Martha Vicinus, Simon Watney, Harriet Whitehead, John J. Winkler, Monique Wittig et Yvonne Yarbro -Bejarano
Keywords: approches et analyses; corps; cours; discours dominant; histoire et politique; hétérosexisme; lesbianisme; outils; ouvrages de références; racisme; santé; sexualité; soc2014; système colonial; systèmes d'oppressions; thématiques; violences

Only words - MacKinnon, Catharine A. (Harvard University Press, 1993)
When is rape not a crime? When it's pornography--or so First Amendment law seems to say: in film, a rape becomes "free speech." Pornography, Catharine MacKinnon contends, is neither speech nor free. Pornography, racial and sexual harassment, and hate speech are acts of intimidation, subordination, terrorism, and discrimination, and should be legally treated as such. Only Words is a powerful indictment of a legal system at odds with itself, its First Amendment promoting the very inequalities its Fourteenth Amendment is supposed to end. In the bold and compelling style that has made her one of our most provocative legal critics, MacKinnon depicts a society caught in a vicious hypocrisy. Words that offer bribes or fix prices or segregate facilities are treated by law as acts, but words and pictures that victimize and target on the basis of race and sex are not. Pornography--an act of sexual domination reproduced in the viewing--is protected by law in the name of "the free and open exchange of ideas." But the proper concern of law, MacKinnon says, is not what speech says, but what it does. What the "speech" of pornography and of racial and sexual harassment and hate propaganda does is promote and enact the power of one social group over another. Cutting with surgical deftness through cases of harassment in the workplace and on college campuses, through First Amendment cases involving Nazis, Klansmen, and pornographers, MacKinnon shows that as long as discriminatory practices are protected as free speech, equality will be only a word.
Keywords: 1900-1999; 1990-1999; amériques; approches et analyses; cours; discipline; droit; histoire et politique; patriarcat; premier cycle; périodes historiques; régions géographiques; science politique et droit; sciences humaines; sciences sociales; sex1911; sexisme; sexualité; sofia; systèmes d'oppressions; thématiques; violences; états-unis; études de genres

Kanehsatake 270 ans de résistance - Obomsawin, Alanis; Koenig, Wolf; Dionne, Claude; Teufel, Dagmar; Vallée, Jacques; Office national du film du Canada (Office national du film du Canada, 1993)
"Par une chaude journée de juillet 1990, une confrontation historique a propulsé les problèmes des Autochtones de Kanehsatake et du village d'Oka au Québec au premier plan de la scène internationale et de la conscience des Canadiens. Au cours de cet été épuisant, la productrice et réalisatrice Alanis Obomsawin, elle-même Indienne abénaquise, a passé 78 jours et nuits angoissants derrière les barricades dressées par les Mohawks, à tourner des images du conflit armé les opposant à la Sûreté du Québec et l'Armée canadienne."--Conteneur.
Keywords: 1900-1999; 1990-1999; Kanehsatake; amériques; approches et analyses; canada; cinéma; communication; cours; discipline; féminisme autochtone; justice sociale; militance; oka; premier cycle; premières nations; périodes historiques; québec; régions géographiques; résistance; sex2283; thématiques; violences

The interpretation of the flesh: Freud and femininity - Brennan, Teresa (Routledge, 1992)
The 'riddle of femininity', like Freud's reference to women's sexuality as a 'dark continent', has been treated as a romantic aside or a sexist evasion rather than as a problem to be solved. In this first comprehensive study, Teresa Brennan suggests that by placing these ideas in the context of Freud's work as a whole, we will begin to understand why femininity was such a riddle for Freud. Brennan argues that by turning to Freud's work and his concrete questions about femininity, a psychical state which occurs in men and women alike, the problem is clearly a soluble one, provided that Freud's concern with energy is taken into account. The real riddle of femininity is as much a problem for thinking about physicality as a problem for the subject who suffers from what Freud described as 'femininity's negative effects on curiosity, intelligence and activity.
Keywords: 1900-1999; cours; discipline; fem1000; féminité; histoire; premier cycle; psychanalyse; psychologie; périodes historiques; ressource en ligne; sciences; sciences humaines; thématiques; violences

Unruly women: The politics of social and sexual control in the old South - Bynum, Victoria E. (Gender & American culture, 1992)
In this richly detailed and imaginatively researched study, Victoria Bynum investigates "unruly" women in central North Carolina before and during the Civil War. Analyzing the complex and interrelated impact of gender, race, class, and region on the lives of black and white women, she shows how their diverse experiences and behavior reflected and influenced the changing social order and political economy of the state and region. Her work expands our knowledge of black and white women by studying them outside the plantation setting.Bynum searched local and state court records, public documents, and manuscript collections to locate and document the lives of these otherwise ordinary, obscure women. Some appeared in court as abused, sometimes abusive, wives, as victims and sometimes perpetrators of violent assaults, or as participants in illicit, interracial relationships. During the Civil War, women frequently were cited for theft, trespassing, or rioting, usually in an effort to gain goods made scarce by war. Some women were charged with harboring evaders or deserters of the Confederacy, an act that reflected their conviction that the Confederacy was destroying them.These politically powerless unruly women threatened to disrupt the underlying social structure of the Old South, which depended upon the services and cooperation of all women. Bynum examines the effects of women's social and sexual behavior on the dominant society and shows the ways in which power flowed between the private and public spheres. Whether wives or unmarried, enslaved or free, women were active agents of the society's ordering and dissolution.
Keywords: 1800-1899; amériques; approches et analyses; civil war; cours; discipline; féminisme matérialiste; his4443; histoire; histoire des femmes*; histoire et politique; intersectionnalité; premier cycle; périodes historiques; racisme; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sexualité; systèmes d'oppressions; thématiques; violences; états-unis

Les femmes autochtones et la justice pénale - Jaccoud, Mylène (Criminologie, 1992)
The interest in understanding and analyzing the situation of native women within the penal process is recent and seems to be limited by the inordinate attention paid by researchers to the overrepresentation of native women. This article is an account of the findings and analyses made to date in this recent sector of research. It presents an inventory of the principal data concerning the confrontation of native women with the penal process. It proposes a synthesis of the principal analyses of the problems of native women with the system of justice by presenting a critical analysis of the socio-structural model of LaPrairie.
Keywords: amériques; approches et analyses; canada; cours; criminologie; discipline; droit; droits des femmes*; droits des femmes* autochtones; histoire et politique; intersectionnalité; justice sociale; pol4105; premier cycle; racisme; régions géographiques; science politique et droit; sciences humaines; sexisme; système colonial; systèmes d'oppressions; thématiques; violences

Sisters in the struggle - Brand, Dionne; Stikeman, Ginny (1991)
Ce documentaire présente des femmes noires actives en politique ainsi que dans l'organisation communautaire, syndicale et féministe. Ils partagent leurs idées et leurs témoignages personnels sur le double héritage du racisme et du sexisme, liant leurs luttes personnelles à la bataille en cours pour mettre fin à la discrimination systémique et à la violence contre les femmes et les personnes de couleur.
Keywords: amériques; approches et analyses; canada; cours; fem3300; militance; premier cycle; racisme; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions; thématiques; violences

Emprise et violence maternelles: étude d'anthropologie psychanalytique - Couchard, Françoise (Psychismes, 0335-492X, 1991)
A partir d'exemples culturels et de cas empruntés à la clinique quotidienne, cet ouvrage montre les effets psychologiques d'une réduction de la personnalité féminine à sa seule fonction de reproduction : en particulier les comportements d'agression de la mère vis-à-vis de sa ou de ses filles.
Keywords: 1900-1999; anthropologie; cours; discipline; europe; fem1000; figure de la mère; france; maternité; premier cycle; psychanalyse; périodes historiques; régions géographiques; sciences humaines; thématiques; violences; violences familiales

Mapping the margins: Intersectionality, identity politics, and violence against women of color - Crenshaw, Kimberlé William (Stanford Law Review, 1991)
Contemporary feminist and antiracist discourses have failed to consider the intersections of racism and patriarchy. To overcome this difficulty, an original approach is suggested here: that of intersectionality. In the first part, the paper discusses structural intersectionality, the ways in which the location of women of color at the intersection of race and gender makes their real experience of domestic violence, rape, and remedial reform qualitatively different from that of white women. The focus is shifted in the second part to political intersectionality, with the analysis of how both feminist and antiracist politics have functioned in tandem to marginalize the issue of violence against women of color. Finally, the implications of the intersectional approach are addressed within the broader scope of contemporary identity politics.
Keywords: 1900-1999; OFDIG; afro-féminisme; amériques; antiracisme; approches et analyses; cours; cycles supérieurs; fem9000; femmes* afro-américaines; féminismes noirs; incontournable; intersectionnalité; militance; patriarcat; périodes historiques; racisme; ressource en ligne; régions géographiques; systèmes d'oppressions; thématiques; violences; violences contre les femmes*; violences raciales; états-unis

Daughters of the dust - Dash, Julie (Cohen Film Collection, 1991)
At the dawn of the 20th century, a multi-generational family in the Gullah community on the Sea Islands off of South Carolina – former West African slaves who adopted many of their ancestors’ Yoruba traditions – struggle to maintain their cultural heritage and folklore while contemplating a migration to the mainland, even further from their roots. The first wide release by a black female filmmaker, DAUGHTERS OF THE DUST was met with wild critical acclaim and rapturous audience response when it initially opened in 1991. Casting a long legacy, DAUGHTERS OF THE DUST still resonates today, most recently as a major in influence on Beyonce’s video album Lemonade. Winner of the Cinematography Award and nominated for the Grand Jury Prize in the Dramatic competition at the Sundance Film Festival. Chosen for preservation by the National Film Preservation Board, USA
Keywords: 1900-1999; amériques; antiracisme; approches et analyses; cinéma; communication; cours; discipline; discours dominant; esclavagisme; fem3200; histoire et politique; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions; thématiques; violences; états-unis

Feminist Debates about Women and National Socialism - Grossmann, Atina (Gender & History, 1991)
Keywords: 1900-1999; 1930-1939; 1940-1949; allemagne; cours; discipline; europe; fascisme; his4830; histoire; histoire des femmes*; histoire et politique; historiographie; holocauste; maternité; nazisme; premier cycle; périodes historiques; régions géographiques; sciences humaines; seconde guerre mondiale; thématiques; violences; violences contre les femmes*; violences d'état; violences sexuelles

Queers read this - Anonyme (1990)
Keywords: LGBTQIA2+; VIH; amérique du nord; amériques; approches et analyses; hétérosexisme; identités LGBTQIA2+; militance; privilèges; queer; ressource en ligne; régions géographiques; systèmes d'oppressions; thématiques; violences; états-unis

Carol - Highsmith, Patricia (Calmann-Lévy, 1990)
Elles se regardèrent au même instant. Thérèse avait levé les yeux de la boîte qu’elle était en train d’ouvrir et la femme venait de tourner la tête vers elle. Elle était grande et blonde, longue silhouette gracieuse dans un ample manteau de fourrure, qu’elle tenait entrouvert, la main posée sur la hanche. Ses yeux étaient gris, décolorés et pourtant lumineux comme le feu, et ceux de Thérèse, captifs, ne purent s’en détacher. Elle entendit la cliente qui lui faisait face répéter une question et elle resta muette. La femme la regardait, elle aussi, l’air préoccupé comme si une partie de son attention était fixée sur l’achat qu’elle s’apprêtait à faire et, bien qu’il y eût plusieurs vendeuses entre elles deux, Thérèse fut certaine qu’elle allait venir vers elle. Carol est le récit d’une obsession. Refusé à l’origine par son éditeur américain, ce roman a paru une première fois en France sous le titre Les Eaux dérobées signé du pseudonyme de Claire Morgan. Sa réédition permet de redécouvrir l’un des ouvrages les plus marquants du XXe siècle, injustement méconnu. Si le sujet ne fait aujourd’hui plus scandale, Carol conserve son odeur sulfureuse et figure parmi les oeuvres cultes de la littérature lesbienne. Patricia Highsmith y dévoile avec force et sensibilité un amour qui revendique sa liberté dans l’Amérique des années 50.
Keywords: 1900-1999; 1950-1959; amour; amériques; histoire et politique; identités LGBTQIA2+; personnes lesbiennes; périodes historiques; roman; régions géographiques; sexualité; thématiques; violences; états-unis

Homeplace : a site of resistance dans Yearning: race, gender, and cultural politics - Hooks, Bell (Yearning: race, gender, and cultural politics, 1990)
bell hooks crosses boundaries in major debates on postmodern theory, cultural criticism, and the politics of race and gender. She warns that “discourse” about “difference” is dangerously detachable from more essential struggles.
Keywords: 1900-1999; 1980-1989; afro-féminisme; amérique du nord; amériques; antiracisme; approches et analyses; cours; discipline; féminisme afroaméricain; histoire et politique; patriarcat; premier cycle; périodes historiques; racisme; régions géographiques; sciences humaines; soc3113; sociologie; systèmes d'oppressions; thématiques; violences; états-unis

Queer Nation Manifesto - Queer Nation (Infokiosk, 1990)
Texte d’un manifeste initialement distribué par des personnes marchant aux côtés du contingent d’Act Up à la Gay Pride de New York, 1990.
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; act up; amériques; approches et analyses; cours; gay pride; manifeste; militance; new york; premier cycle; périodes historiques; queer; régions géographiques; santé; sexualité; soc2014; thématiques; violences; états-unis